Logistics 4.0 and supply chain in production engineering: technological advances and challenges in the digital age - Souza, Hertiquitefanio J. dos Santos; Rosa, Jordan Lavanholle; Cardozo, Noamy Lima; Souza, Noele Bissoli Perini; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2025)
This article analyzes the technological advances and challenges inherent to Logistics 4.0 and Supply Chain 4.0 in the context of Production Engineering. There is a growing adoption of emerging technologies, such as the Internet of Things (IoT), Artificial Intelligence (AI), Big Data, and Blockchain, which favor connectivity, automation, and real-time data analysis. The ProKnow-C methodology was used to support the research, enabling the careful selection and analysis of relevant scientific publications produced between 2010 and 2024. The results demonstrate significant benefits, such as increased operational efficiency, traceability, and strategic planning capabilities, and present examples of applications in companies that have already implemented these technologies. However, challenges such as high implementation costs, the complexity of technological integration, and the need for professional qualifications still constitute barriers to large-scale adoption. The conclusion is that, to ensure effective digital transformation, organizations must develop adaptive strategies, combining innovation with overcoming identified challenges. This process is essential for making operations more agile, competitive, and aligned with the demands of the contemporary market.